Conditions De Travail Et De Vie Des Enfants Dans Le Secteur Informel A Abidjan : Cas Des Adolescentes Dans Le Petit Commerce - Doppon Ali, Coulibaly (European Scientific Journal, ESJ, 2018)
This study aims to analyze the working and living conditions of teenagers in the informal sector of the small business in Abidjan. To achieve this goal, the following hypothesis has been formulated: The difficult working and living conditions of adolescent girls in the informal sector favor the development of deviant or marginal behaviors (begging, prostitution, theft, delinquency, violence, etc.). Victimological theories and criminological theories of acting out were used. The methodological approach took into account the documentary research, the inquiry by interview as well as the phenomenological method, the ethnographic method and the dialectic. The study was conducted among 150 respondents. The route technique has been associated with the area technique for the conduct of the field survey. Qualitative and quantitative analysis were used. The results of this research reveal that it is the combination of internal and external factors with households (socio-economic and cultural conditions) that explains the exploitation of children. These factors must be seen simultaneously in the sense that the exploitation of children remains a social and almost structural phenomenon. In this sense, the study reveals the preponderant role of social capital (kinship and other social norms) that has been neglected in the economic analysis of child labor. In fact, by its ambivalence, work participates in material life as well as in social life.